Diagnosis of single stuck-at faults and multiple timing faults in scan chains. - Chien-Mo Li, J. (IEEE Transactions on VLSI systems)
A diagnosis technique to locate single stuck-at faults and multiple timing faults in scan chains is presented. This technique applies single excitation (SE) patterns, in which only one bit is flipped in the presence of multiple faults. With SE patterns, the problem of unknown values in scan chains is eliminated. The diagnosis result is therefore deterministic, not probabilistic. In addition to the first fault, this technique also diagnoses the remaining timing faults by applying multiple excitation patterns. Experiments on benchmark circuits show that average diagnosis resolutions are mostly less than five, even for the tenth fault in the scan chain.